The Effects of Diuresis, Duration of Dialysis and Age on Lower Urinary Tract Function in Urologically Healthy Male Patients on the Waiting List for Kidney Transplant - Zachoval, Roman; Borovicka, Vladimir; Marada, Tomas; Viklicky, Ondrej; Fronek, Jiri; Krhut, Jan; Janousek, Libor; Slatinska, Janka; Nencka, Petr (Urology Journal, 2018)
Purpose: This work investigated the effects of diuresis, duration of dialysis and age on lower urinary tract function in urologically healthy males on the waiting list for kidney transplant. Materials and methods: The study included all men who had kidney transplants at our centre between January 2009 and December 2014 who had normal urological findings prior to inclusion on the list. Diuresis, the duration of haemodialysis, age, and parameters of function of the lower urinary tract as determined by filling and voiding cystometry were evaluated. Results: The study included 127 men (median age, 59 years; median diuresis, 250 mL; median duration of dialysis, 469.5 days). We found that greater diuresis was accompanied by significantly higher FDV, FDV/Cmax, NDV,Cmax and compliance and by significantly lower Pdet.max, PdetQmax and BOOI. Longer duration of dialysis was accompanied by significantly lower FDV, NDV and Cmax, compliance and Qmax.p and with significantly higher Pdet.max, PdetQmax and BOOI. Older age was associated with significantly higher Pdet.max and with significantly lower compliance. Worsening of the basic parameters of the storage function of the lower urinary tract occurred when diuresis decreased to 500–750 mL, when the duration of dialysis was one year and when patients were older than 54 years. Conclusion: In healthy male patients on the waiting list for kidney transplant, there were connections between the occurrence of dysfunctions of the lower urinary tract and diuresis, duration of dialysis and age. Patients should be monitored for dysfunctions of the lower urinary tract before and after transplantation.